Methodology of ECG Interpretation in the Dalhousie Program; NOVACODE ECG Classification Procedures for Clinical Trials and Population Health Surveys - Rautaharju, P. M.; MacInnis, P. J.; Warren, J. W.; Wolf, H. K.; Rykers, P. M.; Calhoun, H. P. (Methods of Information in Medicine, 1990)
The Dalhousie ECG Program was designed specifically for the needs of epidemiologic studies, health surveys, and clinical trials. The program logic is dynamic in that it can accommodate any combination of ECG leads, record length and sampling rate. The NOVACODE module of the program classifies ECGs according to the Minnesota Code, supplemented with new sets of logic criteria for conduction defects, acute myocardial infarction, and serial ECG changes. Improved statistical models are incorporated for enhanced detection of myocardial infarction using the Cardiac Infarction Injury Score, and for quantification of left ventricular mass estimation. It is anticipated that these program improvements will enhance its utility particularly in monitoring progression and regression of cardiac involvement in hypertensive and ischemic heart disease, and in the assessment of the effectiveness of intervention on cardiovascular disease risk factors.
Keywords: ECG Criteria – Myocardial Infarction; Left Ventricular Hypertrophy; QT Interval – Conduction Defects